Analysis of Soil Resistance under Horizontal Load of Rigid Antislide Pile. (8th October 2021) - Song, Zhenyu; Kong, Yuanyuan; Wang, Siqi; Zhao, Weifeng; Chen, Lu; Feng, Kai
Abstract : In order to study the bearing characteristics and failure mechanism of the rigid antislide pile under horizontal load, the stress of rigid antislide pile under transverse axial large displacement load is analyzed by using elastic-plastic theory, finite element analysis, and model test. The theoretical formula of the proximal plastic earth pressure near the pile with the depth of soil under the horizontal force is obtained. The results show that the standard is insensitive to the variation of soil parameters and the influence of soil parameters on allowable soil resistance in front of pile should be considered. With the increase of the horizontal force of the pile top, the soil near the pile is destroyed in this process gradually, which is the decline of the cross section of the maximum soil resistance of the pile. When the horizontal displacement of pile top is 20 mm and 70 mm, the soil resistance value and the ultimate soil resistance value in front of the pile can be selected, respectively. The plastic zone develops to the front and bottom of the pile at the same speed, at an angle of 45° with the direction of gravity. When the displacement reaches 34 mm, the plastic zone develops to the deeper depth obviously. The results can provide a theoretical basis for the design and application of antislide piles during the process of slope protections.